2009
DOI: 10.1051/radiopro/20095134
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulations of semi-infinite clouds of radioactive noble gases

Abstract: Abstract. Health Canada maintains detector networks across Canada. One of these networks consists of NaI(Tl) detectors that measure air KERMA [1]. Located beside the NaI(Tl) detector in Ottawa is a radioxenon analyzer [2] that measures the activity concentration of 131m,133m,133,135 Xe directly. The ICRUaccepted KERMA to activity concentration conversion factor for 133 Xe, for a semi-infinite cloud measured 1 m off the ground, is 9.68 pGy/hr per Bq/m 3 [3]. However, on various dates, the two detectors in Otta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…2 the 135 Xe/ 133 Xe ratio for the 12 h period release from the medical isotope production facility stack is shown with the 135 Xe/ 133 Xe ratio as measured by a NaI detector located at the Sheenboro measurement site. This information was provided in dose rate and was converted to activity concentrations using conversion factors of 2.6 pGy/h per Bq/m 3 for 133 Xe and 55.10 pGy/h per Bq/m 3 for 135 Xe [23]. Ratios were only calculated when the activity concentration of both isotopes exceeded their respective detection limits of 3.85 Bq/m 3 for 133 Xe and 0.45 Bq/m 3 for 135 Xe [24].…”
Section: Methodsmentioning
confidence: 99%
“…2 the 135 Xe/ 133 Xe ratio for the 12 h period release from the medical isotope production facility stack is shown with the 135 Xe/ 133 Xe ratio as measured by a NaI detector located at the Sheenboro measurement site. This information was provided in dose rate and was converted to activity concentrations using conversion factors of 2.6 pGy/h per Bq/m 3 for 133 Xe and 55.10 pGy/h per Bq/m 3 for 135 Xe [23]. Ratios were only calculated when the activity concentration of both isotopes exceeded their respective detection limits of 3.85 Bq/m 3 for 133 Xe and 0.45 Bq/m 3 for 135 Xe [24].…”
Section: Methodsmentioning
confidence: 99%
“…We assumed the condition of just after radionuclide descent from the atmosphere onto the ground and did not consider ground roughness and initial migration into the ground. The cloud sources, whose volume and activity were 1 × 1 × 1 m 3 and 1 kBq/m 3 , respectively, were located in the air at altitudes of 1, 5, 10, 20, 30, 40, 50, 60, 80, 100, 125, 150, 200, 350, 500, 750, and 1000 m. We used the reciprocal transform method with the receptor and source [ 22 , 23 ] in this process to obtain the results for all sources at once. A previous study [ 24 ] reported that the size of the dose-response function was sufficient to consider dose contributions from distant sources of the radionuclides.…”
Section: Methodsmentioning
confidence: 99%
“…These detectors are set up to report air KERMA for health physics concerns, but after careful study, we can convert these values to activity concentration [8,9]. This careful study was a result of understanding the radioxenon transport down the Ottawa Valley [1].…”
Section: The Nai(tl) Network (Fixed Point Network)mentioning
confidence: 99%